Synthesis of new 1,3-disubstituted-2,3-dihydro-1H-naphth-[1,2e][1,3]oxazines - Turgut, Zuhal; Pelit, Emel; Koycu, Adem (MOLECULAR DIVERSITY PRESERVATION INTERNATIONAL, 2007)
1,3-Disubstituted-2,3-dihydro-1H-naphth[1,2-e][1,3]oxazines were prepared through the ring-closure reactions of the aminobenzylnaphthols with substituted aryl- and heteroarylaldehydes.
Keywords: biological activity; ring-closure reactions; naphth-1,3-oxazines; amino-benzylnaphthols; RING-CHAIN TAUTOMERISM; N-ALKYLATION; Biochemistry & Molecular Biology; Chemistry